Peran Profitabilitas Dalam Memoderasi Pengaruh Debt Covenant, Insentif Pajak, Dan Institutional Ownership Terhadap Konservatisme Akuntansi - Lydya; Riswandari, Ernie (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2026)
Accounting conservatism is an important principle to present financial statements with caution, especially in uncertain economic conditions. However, its application still raises various pro and con arguments. The purpose of this study is to determine the effect of debt covenants, tax incentives, and institutional ownership on accounting conservatism which will be moderated by profitability. This study uses secondary data form financial reports of consumer non-cylicals sector companies listed on the Indonesia Stock Exchange in 2020-2023. The sample was selected using purposive sampling method with moderated regression analysis. The results found that debt covenants and tax incentives have a negative effect on accounting conservatism, institutional ownership has no effect on accounting conservatism, profitability has a positive effect on accounting conservatism, and profitability succeeded in strengthening the negative effect of debt covenants on accounting conservatism, but profitability didn’t succeed in moderating the effect of tax incentives and institutional ownership on accounting conservatism.